Interrogating Discursive Data: How News Media Narratives Assemble Truths About the Teaching Profession. Issue 5 (3rd September 2018) - Grey, Leslee; Shudak, Nicholas
Abstract : This project provides a framework for interrogating the language often used in media reporting on education, and making those often hidden ideological underpinnings more visible. Explored through this analysis are the language, metaphors, logic, and rhetorical devices used by various news media reporting on educational concerns, and in particular the concerns revolving around teacher quality and teacher preparation, which allow the construction and circulation of specific kinds of knowledge and assert certain kinds of truths. This analysis is guided by the premise that education writ large, which includes the profession of teaching as well as the field of teacher preparation, is charged with helping students, our youngest citizens, develop an understanding of the practices and problems of people-power, self-rule, and shared governance in our democratic society. If education primarily involves preparing students for democratic citizenship, as a long history of scholarship has established (Barber, 2001 ; Bean & Apple, 1995 ; Beard, 1937 ; Dewey, 1916 ; Bode, 1937 ; Giroux, 1989 ; Gore, 1993 ; Gutman, 1999 ; McLaren, 2001 ; Nussbaum, 2010 ), educating citizens to critically examine, analyze, and understand social worlds is essential to democracy.